STUDENTS' KNOWLEDGE OF THE GENERATION PLANNING PROGRAM AT SMP NEGERI 8 YOGYAKARTA AS A POPULATION ALERT SCHOOL - Dian Azizah Sadrianysah Wijaya; Anik Widiastuti; Agustina Tri Wijayanti; Daffa Fakhri Maulana; Hendri Irawan (Jurnal Biometrika dan Kependudukan, 2026)
Population is a crucial issue in Indonesia. Population aspects play a crucial role in national development. One way to prepare for development is to develop quality human resources. Adolescents are the spearhead of national development. Therefore, the government needs to guide to adolescents, one of which is through the GenRe program. This study aims to measure the level of students' knowledge about the GenRe program implemented at  State Junior High School 8 Yogyakarta as a Population Alert School. This is a quantitative study using descriptive statistical analysis to process and analyze the data. The population of this study was 960 students at State Junior High School 8 Yogyakarta, and the sample was chosen by using the proportionate stratified random sampling. The data were collected by using a closed-ended questionnaire instrument with a Likert scale, consisting of 6 indicators. Before the questionnaire was administered to respondents, its validity and reliability were tested to ensure the reliability of the research instrument. Based on the results of the study regarding the level of students' knowledge of the Generation Planning program at State Junior High School 8 Yogyakarta, it can be concluded that overall, students demonstrated a good level of knowledge of the program.